2(a-b)²(a+b)-(b-a)²(3a-b)因式分解
来源:学生作业帮助网 编辑:六六作业网 时间:2025/02/07 08:02:45
2(a-b)²(a+b)-(b-a)²(3a-b)因式分解2(a-b)²(a+b)-(b-a)²(3a-b)因式分解2(a-b)²(a+b)-(b-a
2(a-b)²(a+b)-(b-a)²(3a-b)因式分解
2(a-b)²(a+b)-(b-a)²(3a-b)因式分解
2(a-b)²(a+b)-(b-a)²(3a-b)因式分解
原式 2(a-b)²(a+b)-(b-a)²(3a-b)
= 2(a-b)²(a+b)-(a-b)²(3a-b)
=(a-b)²[2(a+b)-(3a-b)]
=(a-b)²(3b-a)
原式=2(a-b)²(a+b)-(a-b)²(3a-b)
=(a-b)²[2(a+b)-(3a-b)]
=(a-b)²(3b-a)
掌握公式,数学其实很简单`(*∩_∩*)′
a-b+2b²/a+b
计算题(2a-b)²(4a²+b²)²(2a+b)²
(a²-b²)²+(a²+2b²)² 计算
帮忙化简下a² -b²/a²b+ab²÷(1-a ² +b² /2ab)
[(a+b)²/(a-b)²] X (2a-2b)/(3a+3b) - a²/(a²-b²)X b/a 的值如题
(a²+b²)-4a²b²因式分解
a²b²-a²-b²+1 因式分解
先化简再求值(a-b/a+b)+(a+b/a-b)-(2a²-2b²/a²+b²)其中a=-2,b=0.5
(2a-3b)²-(b+a)²
ab³-2a²b²+a³b
因式分解:a²-2a(b+c)+(b+c)²
9(a+2b)²-4(a-b)²
化简代数式【(a²+b²/a²-b²)-(a-b/a+b)】÷2ab/(a-b)(a+b)²
(a+b)/(2a+2b)乘(a²+b²)/(a²-b²) 计算
化简:a²-ab-2b²/a+b + b²-a²/a三次方-b三次方 * a²+b²+ab
2(a-b)²(a+b)-(b-a)²(3a-b)因式分解
5(a+b)(a-b)-【2(a+b)】²-(a-b)²
因式分解ab+b²+a-b-2